2016
DOI: 10.1038/srep22766
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Homophily and Heterophily

Abstract: Most social interactions do not take place at random. In many situations, individuals choose their interaction partners on the basis of phenotypic cues. When this happens, individuals are often homophilic, that is, they tend to interact with individuals that are similar to them. Here we investigate the joint evolution of phenotypic cues and cue-dependent interaction strategies. By a combination of individual-based simulations and analytical arguments, we show that homophily evolves less easily than earlier stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…These results hold for any symmetric game in which the pay-offs for mutual cooperation are greater than those for mutual defection. This battle and harmony of messages has been reported in the simulation work [ 34 ], but in a death–birth process and different game set-up.
Figure 2.
…”
Section: Introductionsupporting
confidence: 62%
“…These results hold for any symmetric game in which the pay-offs for mutual cooperation are greater than those for mutual defection. This battle and harmony of messages has been reported in the simulation work [ 34 ], but in a death–birth process and different game set-up.
Figure 2.
…”
Section: Introductionsupporting
confidence: 62%
“…P. Ramazi is with Statistical and Mathematical Sciences Department, University of Alberta, Canada and M. Cao is with ENTEG, Faculty of Science and Engineering, University of Groningen, The Netherlands, p.ramazi@gmail.com, m.cao@rug.nl attention since it is a powerful tool in understanding the evolution of cooperation among selfish individuals as reported by biologists, sociologists, economists, etc [21]- [26]. Researchers have found that network topology [27], phenotypic interactions [28], [29], punishment [30], population heterogeneity [31], as well as other components in game setups can all affect the success of cooperators in face of defectors. One stimulating mechanism for the evolution of cooperation that is generally believed to promote cooperation, especially in human societies [32], is direct reciprocity [33].…”
Section: Introductionmentioning
confidence: 99%
“…The primary innovation of evolutionary game theory is that rather than assuming high levels of rationality in individual choices, perhaps a questionable assumption even for humans, strategies and behaviors propagate through populations via dynamic processes. In the biological world, this propagation is manifested through survival of the fittest and reproductive processes, which are widely modeled using population dynamics [1,7,8]. Systems of first-order differential equations such as replicator dynamics (RD) provide an elegant and powerful means to investigate collective behaviors, assuming infinite and well-mixed populations.…”
Section: Introductionmentioning
confidence: 99%